POLITICAL VIOLENCE IN SINALOA: THE CASE OF THE “PATIENTS” 1972-1978 (PLACES AND MEANS FOR THE RADICALIZATION) - Sánchez Parra, Sergio Arturo (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2012)
This article explores the spaces such as “Comités de Lucha”(fight committees) and “Casas del Estudiante” (student´s houses) as places of sociability, where the radical gesture and legitimization of the use of violence as strategy to take power in Mexico by a student group at the Universidad Autónoma de Sinaloa, called “Los Enfermos” (The sick). It also explores the textual productions. Newspapers, pamphlets, poetry or the practice of reading in these areas of deployment of the dynamic relation were carried out as a part of a set of strategies to promote education policy, to sensitize its members on the need to take up arm against the State of Mexico, and to destroy, if necessary, to set up the dictatorship of the proletariat. This politization process acquired prior to the mobilization and armed combat had a special character: the “revolutionary students” in the Sinaloa entity, located in northwestern Mexico between the years 1972 and 1978. This article is concerned with methodology of the political and cultural history, sustained at primary, oral and bibliographical sources.